Off-trial access to experimental cancer agents for the terminally ill: balancing the needs of individuals and society - Chahal, Manik (Journal of medical ethics, 2010)
The development of cancer therapies is a long and arduous process. Because it can take several years for a cancer agent to pass clinical testing and be approved for use, terminal cancer patients rarely have the time to see these experimental therapies become widely available. For most terminal cancer patients the only opportunity they have to access an experimental drug that could potentially improve their prognosis is by joining a clinical trial. Unfortunately, several aspects of clinical trial methodology that are set in place in order to optimise drug development for the benefit of future generations of cancer patients, pose significant limitations to current patient participation. Therefore, several terminal cancer patients believe that they should have the right to access experimental agents that have passed initial safety testing without having to participate in clinical trials. However, granting off-trial access to patients could be detrimental to the scientific process of drug development, and thus could pose significant risks to the health of future patients relying on sound research. Examining this matter through two divergent ethical lenses, rights-based ethics and communitarian ethics, may provide new insight into the issues surrounding the balance between the autonomous rights of current terminal cancer patients, and the needs of future patients and the values of society.